Explicitness of criteria in peer assessment processes for first-year engineering students - Hattum-Janssen, Natascha van (2006)
This article will outline the motives for the implementation of peer assessment as put into action at the first year of the Civil Engineering course of the University of Minho. The implementation of new assessment methods was a consequence of the successful implementation of peer assessment at other engineering courses. During the semester, three assessment moments took place, in which students assessed the work of their peers. Assessment criteria were defined in a negotiation process between students and teacher. The students subsequently graded the work of their colleagues and had to provide a clear justification for each given grade. The aim of this method is to involve students in the subject, enhance their motivation and deepen their learning. Advantages and disadvantages of peer assessment are discussed. The results that have been obtained so far draw attention to the nature of assessment criteria and the corresponding explicitness.